2017
DOI: 10.1007/s10695-016-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of low-molecular-weight vitellogenin 1 (Vg1)-like proteins as nucleotide excision repair (NER) factors in developing zebrafish (Danio rerio) using a transcription-based DNA repair assay

Abstract: Nucleotide excision repair (NER) removes helix-distorting DNA lesions such as UV-induced pyrimidine dimers and cisplatin-induced strand crosslinking. Our earlier studies have identified low-molecular-weight proteins homologous to the 150-kDa vitellogenin 1 (Vg1) as UV-damaged DNA-binding factors expressed in developing zebrafish (Danio rerio). This present study explored if Vg1-like proteins also participated in NER in zebrafish. Immunoblot analysis of affinity-captured 12 h post-fertilization (hpf) zebrafish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Compared to the transcriptional level, the number of differential proteins related to reproduction and lifespan was low, with ZcVg3, Vg1-like, HSP23like and GPCR Mth2-like genes signi cantly up-regulated and TnC genes signi cantly downregulated at both transcriptional and protein levels. The HSP23 gene is mainly associated with diapause of insects and is upregulated during diapause of pupa overwintering in Sarcophaga crassipalpis (Rinehart et al, 2007), the GPCR Mth2 gene plays a role in drug resistance in Musca domestica (Ma et al, 2020), and the Vg1-like gene is involved in nucleic acid excision during the developmental repair process in Danio rerio (Shen et al, 2017). The Vg1-like, HSP23-like, and GPCR Mth2-like genes of female Z. cucurbitae may have similar functions, but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the transcriptional level, the number of differential proteins related to reproduction and lifespan was low, with ZcVg3, Vg1-like, HSP23like and GPCR Mth2-like genes signi cantly up-regulated and TnC genes signi cantly downregulated at both transcriptional and protein levels. The HSP23 gene is mainly associated with diapause of insects and is upregulated during diapause of pupa overwintering in Sarcophaga crassipalpis (Rinehart et al, 2007), the GPCR Mth2 gene plays a role in drug resistance in Musca domestica (Ma et al, 2020), and the Vg1-like gene is involved in nucleic acid excision during the developmental repair process in Danio rerio (Shen et al, 2017). The Vg1-like, HSP23-like, and GPCR Mth2-like genes of female Z. cucurbitae may have similar functions, but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The Xpa protein expression was not detected until 84 hpf. Later, Shen et al (2017) confirmed that the vitellogenin-1-like protein in zebrafish embryos plays a role of UV-damaged-DNA binding factor and revealed its function in postincision step of NER (Shen et al, 2017).…”
Section: Nucleotide Excision Repairmentioning
confidence: 96%